Rapid and sensitive detection of methicillin-resistant Staphylococcus aureus through the RPA-PfAgo system - Chen, Weizhong; Zhang, Jiexiu; Wei, Huagui; Su, Jie; Lin, Jie; Liang, Xueyan; Chen, Jiangtao; Zhou, Rong; Li, Lin; Lu, Zefang; Sun, Guangyu (Frontiers in Microbiology, 2024)
Introduction Both the incidence and mortality rates associated with methicillin-resistant Staphylococcus aureus (MRSA) have progressively increased worldwide. A nucleic acid testing system was developed in response, enabling swift and precise detection of Staphylococcus aureus (S. aureus) and its MRSA infection status. This facilitates improved prevention and control of MRSA infections. Methods In this work, we introduce a novel assay platform developed by integrating Pyrococcus furiosus Argonaute (PfAgo) with recombinase polymerase amplification (RPA), which was designed for the simultaneous detection of the nuc and mecA genes in MRSA. Results This innovative approach enables visual MRSA detection within 55 mins, boasting a detection limit of 102 copies/μL. Characterized by its high specificity, the platform accurately identifies MRSA infections without cross-reactivity to other clinical pathogens, highlighting its unique capability for S. aureus infection diagnostics amidst bacterial diversity. Validation of this method was performed on 40 clinical isolates, demonstrating a 95.0% accuracy rate in comparison to the established Vitek2-COMPACT system. Discussion The RPA-PfAgo platform has emerged as a superior diagnostic tool, offering enhanced sensitivity, specificity, and identification efficacy for MRSA detection. Our findings underscore the potential of this platform to significantly improve the diagnosis and management of MRSA infection.